The Impact of WebQual 4.0 Method Variables on the Quality service of Education - Sitorus, Tosty Maylangi; Purba, Humiras Hardi; Aisyah, Siti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
The main focus of this study is educational institutions with results showing variables and indicators affecting customer satisfaction. A systematic literature review was used in this study, covering Indonesian national journals from 2017 to 2021 at various educational institutions. The review explores common variables used in website quality assessment using WebQual 4.0 and explores gaps within each theme. The results show variables and indicators affecting customer satisfaction. Society 5.0 (society 5.0), is indispensable in the development of the Industry 4.0 revolution where by using WebQual 4.0 the psychological variables that are part of society 5.0 can be one part of the measurement variables from the human aspect in the use of technology. Basically, the measurement object can vary and can be combined with various other service quality measurement methods in educational institutions. So that the measurement results and also the improvement suggestions obtained can be applied directly.